Study The Perils of Science, The Signs of The Scholars of The World and The Hereafter According to Imam Al-Ghazali in Ihya' Al-Ulum Al-Din - Ula, Hani' Ni'matul; Basuki, Basuki (Jurnal Penelitian Pendidikan Islam, 2024)
Science is a sacred thing and has dangers if it is wrong in its use. In order not to misuse knowledge, it is important to know the signs of world scholars and afterlife scholars. This study aims to identify and analyze the dangers of science as well as the characteristics of scholars and the afterlife. according to al-Ghaza>li. The main source in this study comes from the book Ihya>' al-Ulu>m al-Di>n written by Imam al-Ghaza>li and secondary data sources come from journal articles on the concept of science and the concept of scholars or teachers according to Imam al-Ghaza>li in the book Ihya>' al-Ulu>m al-Di>n. The research approach used is library research. The data analysis technique in this study is to use Content Analysis which is centered on procedures to produce valid conclusions by identifying and analyzing and drawing conclusions from them. This research found two concepts, namely: first, science is able to elevate human status but can also destroy humans if misused. Secondly, the prominent difference between the scholars of the world and the afterlife is in its purpose. World scholars have knowledge aimed at the pleasure of the world, while scholars of the afterlife are aimed at the benefit of the afterlife.